Experimental synthesis, functionalized modifications and potential applications of monoelemental zero-dimensional boron nanomaterials. Issue 10 (23rd February 2022) - Yang, Meng; Jin, Hui; Sun, Zejun; Gui, Rijun
Abstract : This review summarizes recent advances in the experimental synthesis, functionalized modifications and potential applications of monoelemental zero-dimensional boron nanomaterials. Abstract : The past decade has witnessed a rapid growth in scientific studies on zero-dimensional (0D) boron nanomaterials, mainly involving boron nanoparticles, boron quantum dots, boron nanodots, boron nanoclusters and functionalized 0D nano-boron structural derivatives. Various types of 0D boron nanomaterials have been experimentally synthesized and modified, exhibiting superior properties and applications in significant fields. Herein, this review systematically summarizes recent progress of monoelemental 0D boron nanomaterials on the basis of synthesis, modifications and applications. Firstly, this review summarizes the experimental synthesis of 0D boron nanomaterials, majorly including mechanical milling, ultrasonic liquid-phase exfoliation, solvothermal treatment, plasma arc synthesis, solid flame synthesis, active dilution self-propagating high-temperature synthesis, halogen stripping and reduction, laser-induced pyrolysis, and integration of multiple synthesis methods. Secondly, functionalized modifications of 0D boron nanomaterials mainly involve ligand protection on the surface, surface ligand coupling with molecules, core/shell nano-structures, internal encapsulation morphology, mixed multicomponent systems, and hybridized and self-assembled systems. Thirdly, potential applications of 0D boron nanomaterials focus on biomedicine therapy, bio-imaging, absorption, sensing, detection, optoelectronic devices, effects on plant and organism growth, ignition and combustion, precursors for material synthesis, etc. Moreover, this review comments on the state-of-the-art related previous studies, and discusses current status, possible challenges and perspectives about synthesis, modification and application aspects of various 0D boron nanomaterials and 0D nano-boron structural derivatives. This review is very useful for numerous researchers from multiple scientific fields and disciplines. This comprehensive review will facilitate further development of low-dimensional functional nanomaterials with controllable structures, excellent properties, multiple functions and high-performance practical applications.